Conflict of Interests of the Central Powers in Transcaucasia (Armenia on the eve of the Constantinople Conference, March-June 1918) - Petrosyan, Gegham (YSU Journal of International Affairs, 2022)
The article covers in details that the Transcaucasia continued to be the focus of new geopolitical realignments of forces, sharp contradictions, conflicts of militarypolitical and economic interests of the Central Powers. Particular attention was paid to the fact that on the eve of the imminent defeat of the Central Powers during the First World War, the newly independent Republic of Armenia found itself in a deep political and economic crisis, continuing to remain in the most difficult vortex of Ottoman Turkey's military-political tactics and diplomatic impasses.
Keywords: Republic of Armenia; Georgia; Azerbaijan; Russia; Germany; Austria-Hungary; Bulgaria; Turkey; Tiflis; Baku; Hovhannes Kajaznuni; Hamo Ohanjanyan